The Analysis Study of Diagnostic Imaging Performance and Accuracy of Peripheral Artery Disease: A Comprehensive Systematic Review - Bramanda Sihar Mulia L Tobing; Anasya Diandra Atmadikoesoemah; Iskandar Zulkarnain (The Indonesian Journal of General Medicine, 2024)
Background: Imaging advancements in diagnosing peripheral artery disease (PAD) are crucial for improving patient outcomes. Digital subtraction angiography (DSA) is the gold standard, but non-invasive techniques like computed tomography angiography (CTA) and magnetic resonance angiography (MRA) are preferred. Photon-counting computed tomography (PCCT) offers superior spatial resolution and reduced beam-hardening artifacts, enhancing the accuracy of detecting and quantifying stenotic disease. Methods: This systematic review adhered to the PRISMA 2020 guidelines, focusing exclusively on full-text articles published in English between 2013 and 2024. Editorials and review articles without a DOI were excluded to ensure high-quality sources. A literature search was conducted across reputable databases, including ScienceDirect, PubMed, and SagePub, to identify relevant studies. Result: This review included eight studies encompassing a total of over 1,000 patients. The methodological quality of the studies was moderate, with some risk of misclassification and verification bias. Each study was critically appraised, providing a comprehensive analysis of the diagnostic imaging performance and accuracy in the evaluation of peripheral artery disease. Conclusion: The study highlights the benefits of PCCT in diagnosing PAD, especially in patients with advanced disease, calcifications, or renal impairment. It offers superior spatial resolution, artifact reduction, and lower contrast media requirements, promising improved diagnostic accuracy.